If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1x + -24 = 0 Reorder the terms: -24 + 4x + -1x = 0 Combine like terms: 4x + -1x = 3x -24 + 3x = 0 Solving -24 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 3x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 3x = 0 + 24 3x = 0 + 24 Combine like terms: 0 + 24 = 24 3x = 24 Divide each side by '3'. x = 8 Simplifying x = 8
| -9(6+g)-2g=-10 | | (3y+5)(8+y)=0 | | f(x)=45+3(5) | | 2(2y)+2(y+42)=360 | | 2.5d-32.7=74.1 | | 3x-28=2x-21 | | 9-2x(4-1)= | | 5x+2x=-63 | | X+[3x+3]=23 | | 2y+(y+42)=360 | | 3-2(8+2m)=m | | ln(x)=32 | | ln(-2m+10)=11 | | 10+3x+16=31 | | 8x=8x-9 | | -5d-6=-11 | | 3(220-11)+14l=203 | | 6c-11=7 | | X^3-2x^2-24x=x^2-2x-24 | | 10b+9=49 | | 2.3(-1.2x+8.2)=2.1x | | 9a-6=39 | | x/5.2=104 | | 5d+8=43 | | 4x=3-15/13 | | (2x-20)+(x+15)=180 | | 5x=2(3x+5) | | 3r-13r=10 | | 5(3x+6)=4(2x+11) | | 10x+50=7x+80 | | 5x=3-9/13 | | 3/4=6y |